Corporate Governance and Sustainability Disclosure: Determinants of SDGs Disclosure in Indonesia - Monica, Nadila Putri; Saputra, Bayu; Nurlita, Syalmah; Hadiyati, Siti Nur (International Journal of Business, Economics, and Social Development, 2025)
Corporate social responsibility includes disclosing the SDGs as a way to show support for sustainable development. The purpose of this research is to examine how gender diversity on corporate boards and other financial variables, such as profitability and leverage, affect the amount of information on Indonesia's progress toward the Sustainable Development Goals (SDGs). utilizing secondary data collected from the annual reports and sustainability reports of public firms in Indonesia from 2021 to 2023, this research employs a quantitative approach to data analysis utilizing the t test, F test, and coefficient of determination test. According to the findings, Profitability does not significantly impact SDGs. A substantial impact on SDGs is shown via leverage. There is a strong correlation between the gender of the board of directors and the SDGs. A key factor influencing SDGs is the gender composition of the commission. Profitability, leverage, gender representation on the board of directors, and gender representation on the board of commissioners all have an impact on the SDGs at the simultaneously.